Book Reviews - Wirth, David A. (Columbia Journal of Environmental Law, 2020)
PUBLIC POLICY FOR CHEMICALS: NATIONAL AND INTERNATIONAL ISSUES. By Sam Gusman, Konrad von Moltke, Frances Irwin & Cynthia Whitehead. Washington: The Conversation Foundation, 1980. Pp. xiv, 144. 8.50.